2005 Review of the Poverty Reduction Strategy Approach : Balancing Accountabilities and Scaling Up Results. (Policy Papers; Policy Paper ;, 2005)
In December 1999, the World Bank (the Bank) and the International Monetary Fund (the Fund) introduced a new approach to their relations with low-income countries, centered around the development and implementation of poverty reduction strategies (PRS) by the countries as a precondition for access to debt relief and concessional financing from both institutions. These strategies were also expected to serve as a framework for better coordination of development assistance among other development partners.